Environmental philosophy and East Asia : nature, time, responsibility - Abe, Hiroshi, 1971-; Fritsch, Matthias; Wenning, Mario, 1978- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book explores the contributions of East Asian traditions, particularly Buddhism and Daoism, to environmental philosophy in dialogue with European philosophy. It critically examines the conceptions of human responsibility toward nature and across time presented within these traditions. The volume rethinks human relationships to the natural world by focusing on three main themes: Daoist and Eurodaoist perspectives on nature, human responsibility toward nature, and Buddhist perspectives on life and nature. By way of discussing East Asian traditions and European thinkers, this collection reveals that the impact of humanity on the environment is shaped not only by distinctive modes of economic production, but also by cultural beliefs and practices. Representing a unique constellation of environmental and intercultural philosophy, the contributions present systematic approaches to the global need for cultivating environmental responsibility across cultures and generations to address the political, ethical, and aesthetic challenges arising from humanity's transformative impact on the natural world. Presenting a critical re-evaluation of human relationships to the natural world in dialogue with East Asian traditions, this will be a valuable resource for students and scholars of Philosophy, Environmental Studies and Asian Studies"--
Editors' introduction / Hiroshi Abe, Matthias Fritsch, Mario Wenning -- Nature and Dao in Huanglao Boshu / David Chai -- Eurodaoism and the environment / Mario Wenning -- Heidegger's Dao and the sources of critique / Matthias Fritsch -- How to inhabit the best of all possible worlds? Environmental responsibility in the light of Leibniz's conception of time / Sabine Baldin -- What is Oriental liberalism? / Hiroshi Abe -- Emptying ecology : Chan Buddhist antinomianism and environmental ethics / Eric Nelson -- Modification of life awareness and its poetic expressions in Japanese literature / Masataka Furusho -- In spite of nature and with time : freedom and responsibility. two Kantian spells and their possible refutation / Thomas Buchheim -- The person-affecting claim, non-identity problem, and future generations / Rui Han -- The deep layers of responsibility or anti-nature in nature / Ryosuke Ohashi -- Corporeality in an ecologically oriented aesthetics of nature / Zhuofei Wang.
Keywords: Environmental sciences -- East Asia -- Philosophy; Environmental responsibility -- East Asia; Environmental responsibility -- Religious aspects -- Taoism; Environmental responsibility -- Religious aspects -- Buddhism; PHILOSOPHY / General; SCIENCE / Environmental Science; SOCIAL SCIENCE / General